(untitled) (Journal of Computational Mathematics, 1993)
To solve a class of operator equations numerically, some general streamline diffusion methods with satisfactory convergence properties are presented in this paper. It is proved that the approximation accuracy is only half a power of h, the mesh size, from being optimal when these methods are applied to mixed problems and convection-diffusion problems.